HUBUNGAN PERTAMBAHAN BERAT BADAN SELAMA KEHAMILAN DENGAN BERAT LAHIR BAYI DI KECAMATAN SUKARAJA KABUPATEN BOGOR TAHUN 2001 - 2003 - Rindang T, Elmy; ., Fatmah; Anies, Anies (GIZI INDONESIA, 2006)
THE RELATIONSHIP BETWEEN WEIGHT GAIN DURING PREGNANCY AND BIRTH WEIGHT IN SUKARAJA SUBDISTRICT, BOGOR IN 2001 - 2003Maternal body weight gain during pregnancy is important for women suffering from wasting when pregnancy started. Many studies in Indonesia show that low maternal weight gain during pregnancy (less than 10 kg) and high prevalence of pregnant women who had cronic energy deficiency (27.6%) are still problem. The objective of the study is to determine relationship between of maternal weight gain during pregnancy and low birth weight (2500-2999 gram) and its related factors. The study desain was cross-sectional, involving 270 pregnant women, at early stages (12 weeks) who delivered a normal body weight and full term babies (> 37 weeks). Data analysis was done using logistic regression. The result showed that the babies with low birth weight (2500-2999 gram)was 47.8 persen with the average weight of 3015 gram. The average of maternal weight gain during pregnancy was 9.098 kg and those who gained less than 9 kg during pregnancy was 48.9 persen. A significant relationship was found birth weight gain during pregnancy (p=0.000, OR 7.28, 95% CI; 4.25-12.46), and energy intake ((p=0.000, OR 5.15, 95% CI; 2.976-8.913). Multivariate analysis shows that the interaction between energy intake and weight gain during pregnancy is statistically significant (p=0.000, OR 5.8, 95% CI; 1.574-21.536). In conclusion, women who had gain weight at least 9 kg during pregnancy and energy intake more than 70 persen RDA might baby between with birth weight of less than 3000 gram. It is important especially to those who get pregnant suffering from wasting.Keywords: weight gain, pregnancy, birth weight